First Words On Dostoevsky's Introductions - Bagby, Lewis (The Unknown Nineteenth Century, 2015)
Dostoevsky attached introductions to his most challenging narratives, including Notes from the House of the Dead, Notes from Underground, The Devils, The Brothers Karamazov, and "A Gentle Creature." Despite his clever attempts to call his readers' attention to these introductions, they have been neglected as an object of study for over 150 years. That oversight is rectified in First Words, the first systematic study of Dostoevsky's introductions. Using Genette's typology of prefaces and Bakhtin's notion of multiple voices, Lewis Bagby reveals just how important Dostoevsky's first words are to his fiction. Dostoevsky's ruses, verbal winks, and backward glances indicate a lively and imaginative author at earnest play in the field of literary discourse.